2020
DOI: 10.2903/sp.efsa.2020.en-1757
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin mixtures in food and feed: holistic, innovative, flexible risk assessment modelling approach:

Abstract: Mycotoxins are toxic compounds mainly produced by fungi of the genera Aspergillus, Penicillium and Fusarium. They are present, often as mixtures, in many feed and food commodities including cereals, fruits and vegetables. Their ubiquitous presence represents a major challenge to the health and well being of humans and animals. Hundreds of compounds are listed as possible mycotoxins occurring in raw and processed materials destined for human food and animal feed. In this study, mycotoxins of major toxicological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 208 publications
(269 reference statements)
1
54
0
Order By: Relevance
“…In addition, modified mycotoxins are commonly found in cereals and in processed foods, co-occurring with the native mycotoxins, as a result of fungal metabolism or the defense mechanism of the infected plant. This issue is of great interest due to the associated risks for human and animal health [ 91 ]. The effect of CC on the occurrence of modified mycotoxins is a neglected area and needs to be evaluated and included in future risk maps on a regional basis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition, modified mycotoxins are commonly found in cereals and in processed foods, co-occurring with the native mycotoxins, as a result of fungal metabolism or the defense mechanism of the infected plant. This issue is of great interest due to the associated risks for human and animal health [ 91 ]. The effect of CC on the occurrence of modified mycotoxins is a neglected area and needs to be evaluated and included in future risk maps on a regional basis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…OTA can also be detected in dried blood spots and quantified using HPLC-MS/MS technique [167,168]. ELISA can also be applied for the analysis of ochratoxin A in plasma and has been widely used for the screening of samples [169][170][171]. Orti et al [172] reported the first method for the analysis of OTA in human urine, but with simultaneous detection of ochratoxin A and aflatoxin B1.…”
mentioning
confidence: 99%
“…Analytical methods for the detection of FB1 are usually based on urine and are done via the HPLC-MS system. The oral bioavailability is generally below 5% for FB1 [171].…”
mentioning
confidence: 99%
“…The topic of the scientific report drafted was ‘Potential risks from aggregated dietary exposure to mycotoxins’ and focused on the UK population. Mycotoxins are toxic secondary metabolites produced by fungi and can cause adverse health effects in both humans and animals (Lee and Ryu, 2017, Palumbo et al., 2020, Smith et al., 2016, Shi et al., 2019, Battilani et al., 2020). Cereals are often the most severely affected crops.…”
Section: Description Of the Work Programmementioning
confidence: 99%